Urban Transformation Towards Premature Obsolescence Of Buildings - Stolz, Beatrice; Li, Jiajia; Wellinger, Steffen (Enquiry The ARCC Journal for Architectural Research, 2025)
A circular development in cities aims to create ecologically regenerative and resilient environments to transition towards a more sustainable future. This involves rethinking how we design, build, and disassemble, favoring reuse and regenerative cycles. The result is longer building lifespans and, therefore, helps reduce CO₂ emissions from the construction sector. For architects and city planners, the challenge lies in balancing between developing densification strategies to limit urban sprawl with preserving the built environment by extending lifecycles. How does densification affect the demolition and lifespan of buildings in neighborhoods, and what are the possible circular transformations? The objectives of this research are to discuss changes in the built environment in relation to densification strategies and reflect on how these changes might support or hinder circular practices. The paper explores the evolution in building stock over time, using the city of Trondheim, Norway, as a case study. First, data on the existing building stock is analyzed to understand the location and age of various building types across different neighborhoods. Buildings are classified into five categories: low-density housing, high-density housing, public services, industrial and work-related buildings, leisure, and smaller constructions (such as garages, cabins, or sheds). This data is then compared with historical records of buildings being demolished and newly built structures from 2012 to 2021 to trace the transformation of the built environment. It includes information on building type, square meters, construction and demolition dates, and location. The data collected from the municipal cadaster is visualised using Geographical Information System (GIS) software to support a spatial neighborhood-based analysis. The results first present differences in the number of demolitions, building projects, and densification across city areas. Next, the study examines the age distribution within the five building categories. Two main findings emerge: variations in the neighborhood densification over the past decade, and differences in building lifespans across areas. This analysis supports projections for future urban developments, and identifies opportunities for circularity. Additionally, comparing the age of the current building stock with that of demolished buildings highlights the premature obsolescence of certain building types. The findings show that some categories are more prone to demolition or new construction. These results are discussed alongside urban planning and densification strategies, offering policy insights and supporting a contextualised approach to circular development.